Description of the postnatal stages formation of the mandible and its implications for the dentistry practice (LLC "Endo Press", 2020)
The mandible in its external and internal structure has marked age differences, which are due to its functional features. Comparing the individual parameters of the mandible in the development process, it may be noted that in the early age periods, immediately after birth, the magnitude of the mandibular body, specifically its alveolar part, occupies most of the bone mass. Then, during the activation of the temporomandibular joint muscles, is a sharp increase parameters occurs. After the eruption of permanent teeth functional equilibrium occurs, which is confirmed by anatomical characteristics. Work is done on the basis craniological (104 objects) and X-ray radiological methods.